Imagens de controle no funcionamento discursivo das formações imaginárias: análise de uma exposição de racismo no Twitter - Oliveira, Sthefanny Saldanha de (2023)
Through the analysis of a tweet thread and the its comments, the objective of this work is to understand how race relations can be represented discursively in imaginary formations. The tweet thread is made by podcaster Déia Freitas, from the Não Inviabilize podcast, and it makes an exposition of racism on the digital social network Twitter. The exposition concerns the reaction of her listeners who, after finding the publication of her photos in a report made by the Trinta e Seis: Quarenzine blog, were surprised to find out that the podcaster is a black woman. In order to understand how race relations can be represented in the the discursive process of imaginary formations, we propose a discursive take on the notions of controlling images (GONZALEZ, 2018; COLLINS, 2019) and outsider (LORDE, 2020), in addition to a reflection about anticipations based on voice and speech (SOARES, 2019; SOARES; PIOVEZANI, 2019; SOARES; BOUCHER, 2020). Assuming discourse as an effect of meanings between A and B and that discursive processes operate from a series of imaginary formations between these positions (PÊCHEUX, 2014), we analyze the tweets that make up the corpus of analysis trying to understand how anticipations regarding voice and speech and controlling images operate in the discursive game between A (podcaster) and B (listeners). The production conditions of this work take into account the circulation of the corpus in the digital space (DIAS, 2018; 2021), addressing the constitution, formulation and circulation (ORLANDI, 2009) of discursive processes in the digital social networks Twitter, Instagram and in podcasts. From the discursive take on the notion of controlling images and the analysis of anticipations based on voice and speech by the listeners, we observe that the "talking properly" can be perceived as a trace historically associated to white subjects, representing, in speech, the colonizing and racist structure of Brazilian social formation.